2009
DOI: 10.1002/ejoc.200900600
|View full text |Cite
|
Sign up to set email alerts
|

Photoacetylation of Diamondoids: Selectivities and Mechanism

Abstract: The photoacetylation of diamondoids (nanodiamonds), in particular [1212]pentamantane, [1(2,3)4]pentamantane, and [123]tetramantane, with diacetyl almost exclusively gives apical acetyl derivatives. The mechanism of the photoacetylation was studied on the basis of a comparative analysis of the experimental deuterium kinetic isotope effects as well as the observed C–H bond substitution selectivities, which were also computed at the B3LYP, B3PW91, and MP2 levels of theory including polarized continuum modeling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…They form a homologous series of well-defined, saturated hydrocarbons and are the smallest possible units of diamond . Many of their properties, such as the chemical inertness, mechanical hardness, or optical transparency are comparable to those of diamond. Besides choosing diamondoids with respect to their structures and sizes, covalent functionalization tailors desired properties of diamondoids for various applications. For instance, it was shown that the optical gap can be significantly tuned by covalent functionalization. The inclusion of CC double bonds is another route to tune the electronic properties of diamondoids. sp 2 –sp 3 Diamondoid oligomers have been synthesized recently . They exhibit an unsaturated bridge between diamondoids, with highly localized π and π* orbitals leading to a significant decrease of optical transition energies. In the solid phase the diamondoid dimers form van der Waals crystals further lowering optical transition energies due to van der Waals interactions of adjacent molecules in the periodic lattice. , Tailoring the optical properties of diamondoid crystallites by the chemical functionalization of their constituents is therefore a possible path for new wide-gap semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…They form a homologous series of well-defined, saturated hydrocarbons and are the smallest possible units of diamond . Many of their properties, such as the chemical inertness, mechanical hardness, or optical transparency are comparable to those of diamond. Besides choosing diamondoids with respect to their structures and sizes, covalent functionalization tailors desired properties of diamondoids for various applications. For instance, it was shown that the optical gap can be significantly tuned by covalent functionalization. The inclusion of CC double bonds is another route to tune the electronic properties of diamondoids. sp 2 –sp 3 Diamondoid oligomers have been synthesized recently . They exhibit an unsaturated bridge between diamondoids, with highly localized π and π* orbitals leading to a significant decrease of optical transition energies. In the solid phase the diamondoid dimers form van der Waals crystals further lowering optical transition energies due to van der Waals interactions of adjacent molecules in the periodic lattice. , Tailoring the optical properties of diamondoid crystallites by the chemical functionalization of their constituents is therefore a possible path for new wide-gap semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…5 The extraordinary physical and chemical properties of diamondoids, such as low surface energies, high densities as well as hydrophobicities, thermal stabilities, and resistance to oxidation, 1,6 paved the way for the use of 1 and 2, which are the most accessible and readily synthesized diamondoids, also in polymer chemistry. 7 As nanometer-sized building blocks (0.5-2 nm) that can be selectively functionalized both at their periphery (CH bond substitutions) [8][9][10] and internally (by replacing the methylene groups with heteroatoms), 11 diamondoids possess unique properties with high potential value for nanotechnology. For instance, diamondoid thiols selfassembled on gold and silver metal surfaces are highly ordered 12 and display pronounced electron emission prop-erties (NEA, negative electron affinity), providing a source of nearly monochromatic photoemitted electrons.…”
mentioning
confidence: 99%
“…Functionalized diamondoids obtained by regioselective reactions offer a wide range of possible shapes in three dimensions. [14][15][16]21,22 In order to specify the location and stereochemistry of substituents, the von Baeyer nomenclature enhanced by stereochemical descriptors as advocated here is the best available system.…”
Section: Stereochemical Aspects In Perimantanes That Have As Dualistsmentioning
confidence: 99%